2015
DOI: 10.1037/pas0000083
|View full text |Cite
|
Sign up to set email alerts
|

The Child Concentration Inventory (CCI): Initial validation of a child self-report measure of sluggish cognitive tempo.

Abstract: Sluggish cognitive tempo (SCT) is characterized by excessive daydreaming, mental confusion, slowness, and low motivation. Several teacher- and parent-report measures of SCT have recently been developed but a child self-report measure of SCT does not yet exist despite clear links between SCT and internalizing psychopathology (for which self-report is often desired). This study examined the initial reliability and validity of the Child Concentration Inventory (CCI), a child self-report measure of SCT symptoms, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
109
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 85 publications
(127 citation statements)
references
References 58 publications
5
109
0
Order By: Relevance
“…Analyses of one sample of children found a high correlation between ratings by mothers and fathers 24 and ratings by teachers and teachers’ aides 23 , and another study reported a high correlation between children’s self-ratings of SCT and teacher ratings 21 . In contrast, correlations were more modest between parent and teacher ratings of children and between young adults’ self-report ratings and ratings completed by their parents (Table 4).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Analyses of one sample of children found a high correlation between ratings by mothers and fathers 24 and ratings by teachers and teachers’ aides 23 , and another study reported a high correlation between children’s self-ratings of SCT and teacher ratings 21 . In contrast, correlations were more modest between parent and teacher ratings of children and between young adults’ self-report ratings and ratings completed by their parents (Table 4).…”
Section: Resultsmentioning
confidence: 92%
“…SCT is also uniquely associated with lower self-reported self-esteem and emotion regulation difficulties when controlling for ADHD 16,21,43,51,52 . Although no study has examined SCT and sleep functioning in children, SCT symptoms remain associated with adults’ daytime sleepiness, poorer sleep quality, and nighttime sleep disturbance when controlling for ADHD symptoms 36,55,56 .…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…For instance, ADHD-IN is consistently associated with higher levels of externalizing behaviors, and this association is unchanged when controlling for SCT; in contrast, SCT is unassociated (parent ratings) or negatively associated (teacher ratings) with externalizing behaviors when controlling for ADHD-IN (Bernad et al 2014Lee et al 2014;McBurnett et al 2014). Additional evidence is found for SCT's external validity in that higher levels of SCT predict higher levels of anxiety, depression, academic impairment, and social impairment even after controlling for ADHD-IN (Becker 2014;Becker et al 2014aBecker et al , 2015Bernad et al 2014Bernad et al , 2015Lee et al 2015;Servera et al 2015;Willcutt et al 2014). …”
mentioning
confidence: 90%
“…Although the SCT construct has been of interest for some time (Becker et al 2014a), only recently have traditional psychometric procedures been used to develop measures of SCT (Barkley 2013;Becker et al 2015;Lee et al 2014;McBurnett et al 2014;Penny et al 2009). These new measures have led to a series of recent studies on SCT's validity.…”
mentioning
confidence: 99%